Penerapan Lembar Kerja Berbasis Proyek Pada Pembuatan Kombucha Untuk Mengembangkan Kinerja Ilmiah Siswa - Nurani, Intan Jati; Sobandi, Sari; Nurhayati, Nurhayati (Program Studi Pendidikan Kimia, FKIP, Universitas Riau, 2025)
21st century education demands a learning approach that is able to develop students' scientific skills contextually and applicatively. This study aims to describe student activities and analyze the development of students' scientific performance through the application of project-based worksheets in kombucha making activities. The method used is pre-experimental with a one-shot case study design. The research subjects consisted of 35 students. The results of the study showed that the implementation of project-based worksheets was carried out very well, as evidenced by the observation results of 91. Students' ability to complete project-based worksheets is in the very good category, with an average score of 89. The students' scientific performance also showed excellent results, with an average score of 100. These findings suggest the use of project-based worksheets on kombucha making is effective in developing students' scientific performance. Therefore, project-based worksheets can be used as an alternative to innovative learning strategies in developing students' scientific skills in the 21st century learning era.